1999
DOI: 10.1111/j.1471-0528.1999.tb08144.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of observer error in antenatal dipstick proteinuria analysis

Abstract: Objective To determine the role of inter-observer error and the influence of training upon dipstick urine DesignMethods Five standard solutions of serum albumin were used to test the accuracy of midwives and nursing auxiliaries involved in dipstick urine analysis at a maternity hospital. The standard solutions were chosen such that they should have resulted in negative (n = 2) and positive (n = 3) dipstick test results, respectively. analysis.A two phase observational and training study.Setting A teaching mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Bell et al used five albumin samples to look at the accuracy of testing and reported a high false positive rate for the two non-proteinuric samples (nursing auxiliaries; 40% and 55% and midwives; 5% and 30%). For the three positive samples both groups recorded false negative rates of between 10-45% [19]. While automated readers had higher sensitivity, they also produced a lower specificity, i.e.…”
Section: Comparison With Previous Workmentioning
confidence: 91%
“…Bell et al used five albumin samples to look at the accuracy of testing and reported a high false positive rate for the two non-proteinuric samples (nursing auxiliaries; 40% and 55% and midwives; 5% and 30%). For the three positive samples both groups recorded false negative rates of between 10-45% [19]. While automated readers had higher sensitivity, they also produced a lower specificity, i.e.…”
Section: Comparison With Previous Workmentioning
confidence: 91%
“…Despite the fact that the reagent stick is the most commonly used proteinuria screening test for preeclampsia, after the assessment of blood pressure (13), its use has been challenged by several authors (2,6,13,14). Meyer et al (2), in 1994, reported that a cutoff point of '' + '' or greater had positive of 92%, with negative predictive value of only 34%.…”
Section: Discussionmentioning
confidence: 96%
“…Assuming no protein and trace amounts as true negative tests, they failed to identify one in every 11 cases (6). Other studies have analyzed the factors causing errors in reagent stick test results, such as urine concentration, urine pH, examiner error (in nonautomated reading), radio-contrast, and glycosuria (4,13,14). The urine PCR proved to be an accurate method for the diagnosis of preeclampsia when correlated with the 24-hour proteinuria (used as gold standard) (1,6,8,15).…”
Section: Discussionmentioning
confidence: 98%
“…Some of these patients, however, probably had ªpre-eclampsiaº with minimal or no increase in blood pressure. The remainder showed only pregnancy-induced proteinuria, which is known to occur occasionally in normal healthy subjects [13,14]. It was not possible to separate these two groups from one another due to the wellknown limitations in any definition of pre-eclampsia [15±18].…”
Section: Resultsmentioning
confidence: 99%